Aproveitamento de oportunidade para criação da empresa CLOSED Redes de Proteção - Santos, Lucas Augusto Perez dos (2019)
The study of this project is focused in a company in the field of installation of building safety networks in the city of Santo André at ABC Paulista as follow: obtain a new supplier for its safety nets with competitive price, as well as compliance with the severe regulatory require-ments of the sector, which raised doubts with the current supplier. This need proved to be a business opportunity for entrepreneurship, notwithstanding the complexity for a beginning en-trepreneur, identified by the research related to the niche of business, product, market, supplier identification with quality certification and other regulatory requirements. This challenge led to the creation of a new company named CLOSED Protection Networks, which focuses its energies on the importation, manufacture and regularization of raw material for the installation of building protection networks, with the quality certification required by Brazilian standards, which is rare among the importers, being an innovation in this activity. The whole process of constitution of the new company involved studies under the most different aspects such as: tax, contractual and business modality. We also considered the competitive forces, strategic alli-ances and risk analysis related to the difficulties identified in the solution adopted. The business has proved to be fully feasible since its planning and its applicability has already been con-firmed since the company is already in effect and has already made its first import and is already winning new customers.